Efficient induction of spawning of Northern leopard frogs (Lithobates pipiens) during and outside the natural breeding season - Trudeau, Vance L; Schueler, Frederick W; Navarro-Martin, Laia; Hamilton, Christine K; Bulaeva, Elizabeth; Bennett, Amanda; Fletcher, William; Taylor, Lisa (Université d'Ottawa | University of Ottawa, 2013)
Abstract Background Amphibian declines are now recognized globally. It is also well known that many anurans do not reproduce easily in captivity, especially when held over long periods, or if they require hibernation before breeding. A simple method to induce spawning and subsequent development of large numbers of healthy tadpoles is therefore required to meet research and conservation goals. Methods The method is based on simultaneous injection of both female and male leopard frogs, Lithobates pipiens (formerly called Rana pipiens) with a cocktail of a gonadotropin-releasing hormone agonist (GnRH-A) and a dopamine antagonist. We call this the AMPHIPLEX method, which is derived from the combination of the words amphibian and amplexus. Following injection, the animals are thereby induced, and perform amplexus and natural fertilization under captive conditions. Results We tested combinations of a GnRH agonist with 2 different dopamine antagonists in L. pipiens in the breeding season. The combination of des-Gly10, D-Ala6, Pro-NHEt9-GnRH (0.4 micrograms/g body weight; GnRH-A) with metoclopramide hydrochloride (10 micrograms/g body weight; MET) or domperidone (DOM) were equally effective, producing 89% and 88% successful spawning, respectively. This yielded more than 44,000 eggs for the 16/18 females that ovulated in the GnRH-A+MET group, and more than 39,000 eggs for the 15/17 females that ovulated in the GnRH-A+DOM group. We further tested the GnRH-A+MET in frogs collected in the wild in late autumn and hibernated for a short period under laboratory conditions, and report a low spawning success (43%). However, GnRH-A priming 24 hours prior to injections of the GnRH-A+MET cocktail in animals hibernated for 5–6 weeks produced out-of-season spawning (89%) and fertilization (85%) comparable to those we observed for in-season spawning. Assessment of age and weight at metamorphosis indicated that L. pipiens tadpoles resulting from out-of-season spawning grew normally and metamorphosed successfully. Conclusion We provide evidence for successful captive breeding of the leopard frog, L. pipiens. This simple protocol can be used to obtain large numbers of eggs in a predictable, timed manner.